Achieving Near Ideal Covertness in NOMA Systems With Channel Inversion Power Control - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola (Institute of Electrical and Electronics Engineers (IEEE), 2022)
In this letter, we propose two resource allocation schemes for covert communication in a downlink NOMA system, where the transmitter can send information simultaneously both to the public and the covert receiver, while maintaining ideal (or near-ideal) covertness with respect to the warden. The covert transmission is concealed by combining NOMA and channel inversion power control, acting as a random source of uncertainty at the warden. The transmission scheme supports zero outage transmission to the public user and non-zero outage transmission to the covert user, while guaranteeing an ideal or near-ideal covertness at the warden, depending on whether the covert user employs single-user decoding or successive interference cancellation (SIC) decoding. In the latter case, we determine the optimal power sharing factor between the public and covert signals that maximizes the average covert throughput, given a predefined fixed transmission rate to the public user. If the channel between the transmitter and the covert receiver is moderate or strong, the SIC decoding, compared to the single-user decoding, leads to much higher covert throughput at the cost of minor degradation of covertness.